New Image Compression/Decompression Technique Using Arithmetic Coding Algorithm - Salman, Nassir H. (Sulaimani Journal for Pure and Applied Sciences, 2017)
Arithmetic coding is a form of entropy encoding used in lossless data compression. In this article, new technique for image compression/decompression based on arithmetic coding decoding was used. The input image is divided into blocks, each block is 32 x 32 , 64 x 64, and 128 x 128 pixels. If the image is not multiple of the block size , the size of what remains of the image is calculated and columns and rows of zero values are added(padding) up to be all the blocks are 32 x 32,64 x 64..etc . The blocks are separated first as a stream for processing. The result is a stream of compressed tables after do arithmetic coding process and the store bytes are calculated during this process. Then compression ratio is calculated. Finally the stream of the compressed tables is recollected for decompressing (reconstruction image after decoding process) and this is done for each block. The algorithm is tested on different images and the results show a high space saving (88-90%), the process is fast, and it is easy to decode the binary bits to recover the original image exactly without any lose.
Keywords: arithmetic coding; image compression; lossless compression technique; decoding